Dietary constituents of broccoli and other cruciferous vegetables: implications for prevention and therapy of cancer - Herr, Ingrid; Büchler, Markus W. (Cancer treatment reviews, 2010)
Over the past several decades, research on the action of bioactive constituents of plants has focused predominantly on their cancer-preventive properties. Today it can be explained why the consumption of fruits and vegetables may lead to a reduced frequency of certain cancer entities and why certain foods have therapeutic effects. Secondary plant products and especially glucosinolates from vegetables of the cruciferae family are supposed to have anti-carcinogenic potential. The present article gives an overview about secondary plant products in general and focuses to mechanisms of preventive and therapeutic effects of cruciferae, particular the brassica family and their famous member broccoli. Also, this article summarizes our knowledge of safety, tolerance and metabolism of glucosinolates and their therapeutic active degradation products isothiocyanates in animals and clinical studies.